STUDIU PRIVIND ATITUDINILE ȘI TEHNICILE FOLOSIRII AȚEI DENTARE LA POPULAȚIA ADULTĂ - Vlad Dănilă; Anca Stupu; Carina Balcoș; Anca Vițalariu; Iulia Săveanu (Romanian Dental Association for Education, 2017)
The purpose of the study was to determine whether there are differences in the level of knowledge and attitudes regarding the use of dental floss among patients presenting in a private dental office and in an ambulatory dental office. Material and Methods: 80 questionnaires containing questions about dental floss technique and general data of patients entering private dentistry and ambulatory dental office at Sf. Spiridon Iasi Hospital for dental treatments. The group consisted of 43 women and 37 men, aged 18 to 62 (mean 30.4.2 ± 5.9 years). Results: More than 50% of participants use dental floss once a day. 30% of respondents do not use dental floss. Patients in private offices use dental floss more frequently than those in the ambulatory. Female subjects tend to use dental floss more frequently than men. 56.3% of the subjects received instructions for the use of dental floss from the dental practitioner. 43.2% of the subjects make upward movements and 32.1% circular movements around the dental crown. 63% of respondents responded that they preferred rounded dental floss and 41.3% use fluorinated dental floss. Conclusions: The frequency of use of dental floss is relatively high. The technique of using dental floss with up and down movements in contact with each tooth surface has been reported as the most common form of cleaning. Subjects attending private practice use daily dental floss, most of them male.